Branding As a Means of Positioning Itself in the Marketplace – A Case Study of the Catholic University Institute of Buea – The Entrepreneurial University (British Journal of Multidisciplinary and Advanced Studies, 2022)
Branding is the process involved in creating a unique name and image for a product in the consumers’ mind, and this happens mainly through advertising campaigns with a consistent theme. It aims to establish a significant and differentiated presence in the market that attracts and retains loyal customers. Brand not only creates loyal customers, but it creates loyal employees and gives them something to believe in, something to stand behind and finally it helps them understand the purpose of the organization or the business. A strong brand is invaluable as the battle for customers intensifies day by day. It’s important to spend time investing in researching, defining, and building your brand after all; your brand is the source of a promise to your consumer. Brand serves as a guide to understanding the purpose of business objectives and it enables the business or a company to align a marketing plan with the objectives and the effectiveness of brand doesn’t just happen before the purchase, but it’s also about the life of the brand of the experience it gives a consumer. A business or companies’ brand is one of your greatest assets and it is not just the logo, slogan and design scheme, but the customers’ total experience of your business.
Keywords: Brand; Branding; Business Objective; Consumers; Marketplace